Income Disparities in Cancer Screening: A Cross-Sectional Study of the Korean National Health and Nutrition Examination Survey, 2013–2019 - Rajaguru, Vasuki; Kim, Tae Hyun; Shin, Jaeyong; Lee, Sang Gyu (Frontiers in Public Health, 2022)
Background: This study examined whether income-related disparities in cancer screening services existed after the national cancer screening program was enacted in Korea. Furthermore, we assessed the contribution of socio-economic factors to disparities in the utilization of cancer screening services and assessed the association between household income and the utilization of cancer screening. Methods: A cross-sectional study of individuals aged over 40 years was conducted using data from the 2013-2019 Korea National Health and Nutrition Examination Survey (KNHANES). The selected variables were socioeconomic characteristics and health status. Household income was categorized into quartiles from Q1 (the lowest income group) to Q4 (the highest income group). Logistic regression analysis was performed to assess associations between cancer screening and individual characteristics. Subgroup analysis was performed according to household income quartiles. Results: There were 20,347 individuals included in this study. Among these, 14,741 (70%) had undergone cancer screening. There existed a gap in the utilization of cancer screening between the lowest (Q1) and highest (Q4) income quintiles owing to evident income disparities; Q4 thus had a significantly higher likelihood of undergoing cancer screening than other quintiles. Female sex, university and over education, number of chronic diseases, and private insurance coverage were positively associated with cancer screening (p < .001). Conclusion: Our findings suggest that policymakers should develop and design strategies to increase awareness and efforts to improve the education and promotion of cancer screening among lower-income target groups.